2021
DOI: 10.3390/microorganisms9122550
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility and Increased Resistance of Bacteria against Disinfectants: A Systematic Review

Abstract: Disinfectants are used to reduce the concentration of pathogenic microorganisms to a safe level and help to prevent the transmission of infectious diseases. However, bacteria have a tremendous ability to respond to chemical stress caused by biocides, where overuse and improper use of disinfectants can be reflected in a reduced susceptibility of microorganisms. This review aims to describe whether mutations and thus decreased susceptibility to disinfectants occur in bacteria during disinfectant exposure. A syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 157 publications
(141 reference statements)
0
26
0
4
Order By: Relevance
“… 1 , 2 It is thus extremely important to enhance our quality of life with environmental bacterial inhibitors because of the ubiquity of pathogenic bacteria. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It is thus extremely important to enhance our quality of life with environmental bacterial inhibitors because of the ubiquity of pathogenic bacteria. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Results in this invitro study showed that Tulsi extract and Curcumin extract showed effective inhibition of growth of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis comparable to 0.2% Chlorhexidine. Although many previous studies conducted have shown antimicrobial properties of Tulsi and Curcumin against oral microbiota, and there is evidence claiming phytomedicinal products being effective against periodontal pathogens 15,16,17,18 ; To the best of our knowledge, this is the first study till date, to evaluate the antimicrobial efficacy of curcumin extract on periodontal pathogens.…”
Section: Discussionmentioning
confidence: 96%
“…MDCs, such as triclosan and parabens, contribute to the AMR issue, primarily through resistance development against themselves (self-resistance), but also potentially through development of cross-resistance against antibiotics ( Ribado et al, 2017 ). Although the evidence supporting cross-resistance development in situ is not conclusive ( Scientific Committee on Consumer Safety [SCCS], 2010 ), the potential contribution of MDCs to AMR and their mechanisms merit further data compilation ( Valkova et al, 2002 ; Hughes et al, 2020 ; Rozman et al, 2021 ). Moreover, given that antimicrobial MDCs would likely have higher potential to alter and perturb microbiomes (compared to non-antimicrobial xenobiotics), they have been proposed as candidate chemicals in investigations that would built our understanding around the xenobiotic-microbiome interactions in the context of xenobiotic RA ( National Academies of Sciences, Engineering, and Medicine [NASEM], 2018 ).…”
Section: Gut Microbiome and Antimicrobial Resistance Under One Healthmentioning
confidence: 99%